SALES PROMOTION, LIVE STREAMING, SUBJECTIVE NORM TERHADAP IMPULSIVE BUYING DENGAN PAYLATER SEBAGAI VARIABEL MODERASI - Salsabilla Ayundha Martsha Buana; Janice Atalie Leow; Gerry Marvinson; Azka Zukhrufa; Keni Keni (Jurnal Bisnis dan Akuntansi, 2023)
E-commerce has profoundly altered the shopping behaviors of consumers in Indonesia. Additionally, fintech companies have introduced "paylater" services, revolutionizing the payment process for online purchases. Paylater operates on a Buy Now Pay Later (BNPL) system, allowing consumers to make purchases and defer payment. This innovation enhances the ease and security of online shopping, enticing users with enticing sales promotions. A survey targeting e-commerce users in Indonesia was conducted and subsequently analyzed using structural equation modeling (SEM - PLS). Employing a quantitative descriptive approach with a cross-sectional design, data was collected offline over 14 days in DKI Jakarta, Indonesia, yielding a final dataset from 122 respondents out of 210 obtained. Research outcomes revealed that sales promotion, subjective norms, and e-commerce live streaming features significantly influence impulsive buying behavior among consumers. The use of paylater services moderates this relationship, indicating that frequent paylater users tend to exhibit more impulsivity in their purchasing patterns. Despite the convenience offered by paylater services, there are associated risks such as debt accumulation and financial mismanagement. The findings of this research can serve as an educational tool for potential paylater users, encouraging responsible use and financial management. This research substantially contributes to the growth of fintech companies and micro, small, and medium-sized enterprises (MSMEs), ultimately fostering economic development and providing a reference for future researchers exploring similar topics.